2015
DOI: 10.1039/c5cc06052d
|View full text |Cite
|
Sign up to set email alerts
|

Bidentate nitroxide ligands stable toward oxidative redox cycling and their complexes with cerium and lanthanum

Abstract: We report the synthesis of 1,3-bis[(2′-tertbutyl)hydroxyaminophenyl]benzene (H2arene-diNOx) and its metal complexes, Ce(arene-diNOx)2 (1) and [(py)2K(18-crown-6)][La(arene-diNOx)2] (2). Electrochemical studies demonstrated that the H2arene-diNOx, bidentate nitroxide ligands significantly stabilized the Ce(IV/III) redox couple to −1.74 V versus Fc/Fc(+). Moreover, a reversible oxidation wave was observed for 1 at −0.37 V, leading to a novel, stable redox-active nitroxide ligand. DFT calculations confirmed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 31 publications
2
23
0
Order By: Relevance
“…Organo-f-block chemistry incorporating redox-active ligands has had an increasing presence in the literature over the last 15 years. Most of these studies have focused on uranium chemistry, but some examples of cerium, ytterbium, europium, samarium, and thorium also exist. Kiplinger and co-workers synthesized 1,2-bis­[(2,6-diisopropylphenyl)­imino]­acenaphthene (BIAN) complexes of uranium­(III) and uranium­(IV) and showed that the charge state of the ligand and the oxidation state of the metal depend on the coordination environment of the complex .…”
Section: Introductionmentioning
confidence: 99%
“…Organo-f-block chemistry incorporating redox-active ligands has had an increasing presence in the literature over the last 15 years. Most of these studies have focused on uranium chemistry, but some examples of cerium, ytterbium, europium, samarium, and thorium also exist. Kiplinger and co-workers synthesized 1,2-bis­[(2,6-diisopropylphenyl)­imino]­acenaphthene (BIAN) complexes of uranium­(III) and uranium­(IV) and showed that the charge state of the ligand and the oxidation state of the metal depend on the coordination environment of the complex .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, [Ce­(O i Pr) 4 (HO i Pr)] 2 and [Ce­(O t Bu) 2 (NO 3 ) 2 (THF) 2 ] were used to access the first well-defined organocerium­(IV) derivatives [(C 5 H 5 ) 3 Ce­(O i Pr)] and [(C 5 H 5 ) 3 Ce­(O t Bu)], respectively. Alternative synthesis methods for well-defined Ce IV alkoxides comprise the oxidation of trivalent precursors, e.g., [Ce­(OC t Bu 3 ) 3 ], with di- tert -butyl peroxide (DPBO) or 1,4-benzoquinone and the recently established alcoholysis of [Ce­{N­(SiHMe 2 ) 2 } 4 ] (p K a (HN­(SiHMe 2 ) 2 ) = 22.6) …”
Section: Introductionmentioning
confidence: 99%
“…From the synthetic perspective, many more molecular Ce 4+ species can be prepared than the handful of available extended solids. , Molecular Ce compounds are usually stabilized in the 4+ formal oxidation state by halides and hard O-donor ligands such as alkoxides and acetylacetonates. , Many “nonclassical” tetravalent Ce molecules have also been prepared, including organometallic compounds, amides, ,, porphyrins, and a variety of other multidentate N-donor ligands. Among these, the lanthanide sandwich molecule cerocene, (C 8 H 8 ) 2 Ce, has played a central role in the development of electronic structure models for tetravalent Ce molecules. Theoretical, magnetic, and L 3 -edge XANES studies of (C 8 H 8 ) 2 Ce resulted in observation of the Kondo effect in a single molecule, a phenomenon that is typically reserved for metals. , More recently, an in-depth Cl K-edge XAS and density functional theory study showed that Cl 3p and Ln 4f covalency was significant in tetravalent CeCl 6 2– but virtually nonexistent in the trivalent analogue, CeCl 6 3– …”
Section: Introductionmentioning
confidence: 99%
“…[68][69] Many "non-classical" tetravalent cerium molecules have also been prepared, including organometallic compounds, [70][71][72] amide, 65,70,[73][74][75][76][77][78] porphyrins [79][80][81][82][83] and a variety of other multidentate N-donor ligands. [84][85][86][87][88][89][90][91] Among these, the lanthanide sandwich molecule cerocene, (C8H8)2Ce, [92][93][94][95][96][97][98][99][100][101][102][103] has played a central role in development of electronic structure models for tetravalent cerium molecules. Theoretical, magnetic, and L3-edge XANES studies of (C8H8)2Ce resulted in observation of the Kondo effect in a single molecule -a phenomenon that is typically reserved for metals.…”
Section: Introductionmentioning
confidence: 99%